Accidents in Laboratories Working with Pathogenic Biological Agents - I. M. Krepostnova; M. V. Gordeeva (Проблемы особо опасных инфекций)
Accidents during the work with infectious disease agents are one of the leading biological risk factors for employees, the public and the environment. Specialists in the field of biological safety should monitor and analyze information on these accidents in order to use the findings and implications to form a sustainable biosafety system both, at the facility and at the federal levels. To obtain the necessary information to analyze the causes and conditions of accidents, we have carried out a search of open data on the Internet. It has been found that the relevant information is more extensively and accessibly presented in foreign sources. Information on accidents that occurred abroad between 2010 and 2023 has been studied. Accidents associated with skin penetration and lesions were most often the obvious cause of laboratory acquired infection. Reports of similar accidents caused by injection needle sticks predominated. Accidents associated with breach of personal protective equipment (torn gloves) were a potential cause of infection when there was a concurrent violation of the skin integrity or in the case of skin lesions existing at the time of the accident. Cases of violation of the integrity of insulating personal protective equipment were described. Reports on accidents “with spillage” and “without spillage” (as stated in the Russian normative documents) have not been found. Among the investigated cases, most are associated with violations of various biological safety requirements.